Effect of NaCl on oxidative stability and protein properties of oil bodies from different oil crops. (October 2019) - Hou, Juncai; Feng, Xue; Jiang, Mengting; Wang, Qiuling; Cui, Chunli; Sun, Changbao; Hussain, Muhammad Altaf; Jiang, Lianzhou; Jiang, Zhanmei; Li, Aili
Abstract: The objective of this study was to determine the effect of different NaCl (0, 50, 100, 150 and 200 mmol/L) on oxidative stability and protein properties of soybean oil bodies (SBOBs), peanut oil bodies (PNOBs) and sunflower oil bodies (SFOBs) at 25 °C. Results showed that, with the increase of NaCl concentration, ζ-potential values of these three oil bodies (OBs) were decreased significantly and then remained stable, and their particle sizes were slightly increased. NaCl did not significantly influence protein composition and thermal properties of these three OBs, but increased their total ΔH of proteins. With 50 mmol/L of NaCl, hydrophobicity and emulsifying activity (EAI) of SBOBs, PNOBs and SFOBs, and emulsifying stability (ESI) of SBOBs were significantly reduced. When NaCl concentration was more 50 mmol/L, the surface hydrophobicity, emulsifying activity of SBOBs, PNOBs and SFOBs, and emulsifying stability of PNOBs and SFOBs were then gradually increased. Under the accelerated oxidation conditions at 60 °C and when NaCl concentrations was 150 mmol/L, peroxide values of these three OBs were lower than that when NaCl concentration was 50 mmol/L or 100 mmol/L. And thiobarbituric acid values (TBARS) of these three OBs with different NaCl concentrations were all relatively low. Highlights: NaCl significantly reduced ζ-potential, emulsifying properties of oil bodies. NaCl significantly increased the average particle size of oil bodies. All of these three oil bodies showed excellent oxidation stability. NaCl can significantly increase total ΔH of oil body protein.